The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000486915
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Neuroendocrine Tumors (G-Nets): Incidence, Prognosis and Recent Trend Toward Improved Survival

Abstract: Background/Aims: Gastric neuroendocrine tumors (G-NETs) are uncommon neoplasms that can present with or without clinical symptoms. In this study, we evaluated the incidence, prognosis, and temporal trends of G-NETs. Methods: We analyzed all cases of G-NETs registered in the Surveillance, Epidemiology, and End Results (SEER) database from 1973 to 2014. Incidence was estimated by age and joinpoint analyses. Survival rates were calculated and survival trends over time were evaluated. Results: A total of 3740 elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…GNENs were an orphan disease and accounted for 6.9% of all the GEP-NENs, representing 0.3-1.8% of all gastric malignancies [17][18][19]. Based on the up-to-date SEER database, our study revealed that the incidence of GNENs has increased gradually in the past 4 decades, consisting with the previous study [1,2,17]. Moreover, it was rapidly increased among those with localized and grade I tumors.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…GNENs were an orphan disease and accounted for 6.9% of all the GEP-NENs, representing 0.3-1.8% of all gastric malignancies [17][18][19]. Based on the up-to-date SEER database, our study revealed that the incidence of GNENs has increased gradually in the past 4 decades, consisting with the previous study [1,2,17]. Moreover, it was rapidly increased among those with localized and grade I tumors.…”
Section: Discussionsupporting
confidence: 70%
“…The incidence of NENs has increased to 6.98/100,000 [1] in 2012 according to the data of Surveillance, Epidemiology and End Results (SEER) database. The increase could be observed among NENs at all sites, especially in gastric NENs (GNENs) with nearly 15-fold in the past 40 years [1], reaching up to 4.85/1,000,000 in 2014 [2]. According to WHO classification of 2010, NENs have been divided into well-differentiated neuroendocrine tumor (NET) and poorly differentiated neuroendocrine carcinoma (NEC) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Various factors had been identified to assess the prognosis of these cases like duration, sex, age group, size, site, grading and staging and other factors. These variables affect the outcome of disease in terms of morbidity and mortality 19 . There were no current or past researches available in the form of randomized control or retrospective studies available on GNET in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed an increased incidence of gastric neuroendocrine tumors from 0.31 per 1 000 000 patients in 1975 to 4.85 in 2014. 27 Gastric NETs have a site-specific distribution depending on the tumor subtype. For example, histamine-producing enterochromaffin-like (ECL) cell NETs arise in the corpus/ fundus while somatostatin-expressing D-cell and gastrinexpressing G-cell NETs occur in the antrum.…”
Section: Gastric Neuroendocrine Neoplasmsmentioning
confidence: 99%